N-terminal Pro-B-type natriuretic peptide, vascular disease risk, and cholesterol reduction among 20,536 patients in the MRC/BHF heart protection study. - Emberson, JR; Ng, L; Armitage, J; Bowman, L; Parish, S; Collins, R; Heart Protection Study Collaborative Group (Elsevier, 2007)
OBJECTIVES: We sought to assess the ability of N-terminal pro-B-type natriuretic peptide (N-BNP) to predict vascular events in high-risk people and to test whether statins benefit people with high levels of N-BNP. BACKGROUND: The predictive value of N-BNP for occlusive vascular events and the effects of statins in people with high N-BNP levels are uncertain. METHODS: A total of 20,536 people were assigned randomly to simvastatin 40 mg daily or placebo for an average of 5 years. Five baseline N-BNP groups were defined ( andlt; 386; 386 to 1,171; 1,172 to 2,617; 2,618 to 5,758; and > or =5,759 pg/ml). RESULTS: Baseline N-BNP was strongly predictive of future vascular events independently of other characteristics. Compared with participants with N-BNP andlt; 386 pg/ml, those with levels > or =5,759 pg/ml had adjusted relative risks for major vascular events (MVEs) (i.e., major coronary events [MCE] [nonfatal myocardial infarction or coronary death], stroke, or revascularization) of 2.26, for MCE of 3.09, for stroke of 1.80, and for heart failure (hospitalization or death) of 9.23 (all p andlt; 0.0001). Overall, simvastatin allocation reduced the relative risk of MVE by 24% (95% confidence interval 19 to 28). There was a trend toward smaller (but still significant) proportional reductions in MVE among participants with greater baseline N-BNP levels, but the absolute benefits of simvastatin allocation were similar at all N-BNP levels. Simvastatin allocation was also associated with a 14% (95% confidence interval 0 to 25) proportional reduction in heart failure. No excess risk of other vascular and nonvascular outcomes was observed with simvastatin allocation among participants with greater baseline values of N-BNP. CONCLUSIONS: In this study, N-BNP levels were strongly predictive not only of heart failure but also of MVEs. In people with high N-BNP levels consistent with heart failure, statin allocation significantly reduced vascular risk, with no evidence of hazard. (http://www.controlledtrials.com/ISRCTN48489393/48489393).